Early Surgical Intervention following Inguinal Hernia Repair with Severe Postoperative Pain - Ferdinand Köckerling; Christine Schug-Pass (Frontiers in Surgery, 2017)
IntroductionSevere postoperative pain is an important risk factor for onset of chronic inguinal pain following inguinal hernia repair. All measures must be taken to eliminate postoperative pain.Materials and methodsThis case report highlights the problems of severe postoperative pain following transabdominal preperitoneal patch plasty (TAPP) inguinal hernia repair and describes a systematic treatment path that may include surgical intervention.ResultsFollowing TAPP operation for lateral inguinal hernia, this patient who had been operated on in an external hospital still experienced intense, stabbing inguinal pain on postoperative day 7 during movement, despite optimal pain treatment. Diagnostic examination did not reveal any findings of note. The surgical report documented that the surgeon had used metallic tacks for mesh fixation, i.e., at the pectineal line of the pubic bone, pubic symphysis, upper margin of the mesh, and for closure of the peritoneum. During surgical revision on postoperative day 7, eight tacks and the mesh were removed and, following further dissection, a new mesh was placed and fixed with glue. The patient’s intense stabbing pain resolved immediately after surgery.ConclusionSince the results of late intervention for chronic inguinal pain are anything but satisfactory, early surgical intervention should be considered for patients with severe postoperative pain >3 days of suspected surgical origin.